Expanding shareholders’ power: An analysis of reform proposals in Malaysia - Mohd. Sulaiman, Aiman @ Nariman (Walter de Gruyter GmbH, 2018)
A series of recent reform proposals in Malaysia have started to consider enhancing shareholders’ self-help remedies by expanding shareholders’ powers in corporate decision-making. The reform of listing rules, codes of corporate governance, and securities law legislation is intended to enhance shareholders’ participatory rights in decision-making in Malaysia. Some of the proposals echo the present UK position under the UK Companies Act 2006. These changes, occurring in several common law countries such as Malaysia, Hong Kong and UK, and the recent EU revision proposals, indicate a change of legal position towards expanding shareholders’ power even to the extent of giving instruction to the board. But are these sufficient or can more be done? For Malaysia and other developing economies, we argue for a self-enforcing model that requires expansion of shareholders’ general power by identifying and removing legal barriers to shareholders’ empowerment. This is recommended for other developing countries which share a similar corporate and regulatory architecture.